Early clinical experience module: single medical school experience during the pandemic - Salihan, Safuraa; Khalid, Mohamed Hanief; Sa’at, Azmah; Chong, Kok Wah; Subramaniam, Shamala Devi (UPM Press, 2022)
The Early Clinical Experience (ECE) module is a module that was introduced to expose preclinical medical students to the clinical skills required for their clinical practice. COVID-19 has forced traditional face-to-face teaching into online mode. In Universiti Putra Malaysia (UPM), the teaching underwent several improvisations to cope with the online mode but still within the framework of four basic components of clinical skills namely history taking, physical examination, basic procedural skills, and communication skills. The advantages and limitations of the usage of online lectures and demonstrations, video recordings, Google Classroom (GC) platform, and written feedback were discussed. In conclusion, the online mode of ECE delivery has its advantages and limitations, and educators need to address these concerns to ensure the future success of the module.